Effect of Pyrolysis Temperature on PhysicoChemical Properties and Acoustic-Based Amination of Biochar for Efficient CO2 Adsorption - Chatterjee, Riya; Sajjadi, Baharak; Chen, Wei-Yin; Mattern, Daniell L.; Hammer, Nathan; Raman, Vijayasankar; Dorris, Austin (Frontiers in Energy Research, 2020)
The present study examined the effect of pyrolysis temperature on the physicochemical properties of biochar, activation process and carbon capture. Two different categories of biochars were synthesized from herbaceous (miscanthus and switchgrass) or agro-industrial (corn stover and sugarcane bagasse) feedstock under four different pyrolysis temperatures- 500, 600, 700 and 800 ºC. The synthesized biochars underwent sono-amination activation comprising low-frequency acoustic treatment followed by amine functionalization to prepare adsorbents for CO2 capture. As per the elemental analysis, the elevated pyrolysis temperature resulted in increased %C and %ash contents and reduced %N contents of biochar. The textural analysis exhibited almost 3-times enhancement of micro surface area and pore volume upon increasing the pyrolysis temperature from 500 to 700 ºC, though further increase to 800 ºC reduced the micro-porosity and the surface area. The intermediate temperatures of 600 and 700 ºC revealed the highest interactions with ultrasound-amination, which significantly intensified CO2 adsorption. Accordingly, the CO2 capture capacity of sono-aminated biochars synthesized at 600 and 700 ºC were almost 200% greater than that of raw biochars. There were 127-159% and 115-151% increases in adsorption capacity of biochars synthesized at 800 and 500 ºC upon ultrasono-amine functionalization. Miscanthus biochar synthesized at 700 ºC and treated sono-chemically demonstrated the highest adsorption ability of 2.89 mmol/g at 70 ºC and 0.10 atm partial pressure, which is 211% higher than its pristine condition. The superior adsorption capacity of miscanthus (at 700 ºC) can be attributed to its large surface area (324.35 m2/g), high carbon content (84%), and low ash content (4.9%), as well as its %N content after sono-amination that was twice that of raw char.